Effect of Cooling Rate on Integrity of Zone-Differentiated Adrenal Cell Populations of Rats - Dudetskaya, G. V.; Bozhok, G. A.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2011)
By means of the fluorescent microscopy and histochemical staining the adult rat adrenal cells prior to and after cryopreservation were studied. Low cooling rates enable the preservation of the highest number of cells in suspension after freeze-thawing. Cooling rates cause a selective effect on preservation of the cells of cortical and medullar substances of adrenal glands.